Pengaruh Kepuasan Kerja Terhadap Turnover Intention Pada CV Surya Nedika Isabella - Candra Yudi Prasetyo Sudarmiani (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2018)
This study aims to determine the effect of job satisfaction on turnover intention ofemployees at the CV Nedika Isabella Kawedanan Magetan, to determine the turnoverintention of employees at the CV Nedika Isabella Kawedanan Magetan, as well as todetermine whether there is influence of job satisfaction on turnover intention on the CVSurya Nedika Isabella Kawedanan Magetan. Determination of the sample in this study usingthe sample Nonprobability sampling technique of sampling Purposive Sampling that is asmuch as 70 employees. The data collection instrument uses a Likert scale questionnaire thathas been tested and validated and validity and reliability. Data analysis using simple linearregression then t test. In releasing the data using the help of SPSS for windows version 22.0.pnenlitian results showed that job satisfaction has a negative effect on turnover intention onthe CV Surya Nedika Isabella Kawedanan Magetan. Results of simple linear regression Y =69.919 - 0,228X, meaning that if the job satisfaction increased by 1%, the turnover intentionfell by 0.228. The results obtained Sighit value is 0.000 while